Biological and ecological characteristics of the cabbage aphid parasite (Eurasian Research Bulletin, 2026)
This article provides a comprehensive analysis of the biological and ecological characteristics of major cabbage pests, particularly the cabbage aphid (Brevicoryne brassicae L.) and the cabbage bug (Eurydema ventralis Kol.), under the environmental conditions of the Khorezm region. The study is based on both field and laboratory experiments conducted during 2024–2025, focusing on their life cycle, reproductive capacity, seasonal development, and adaptation to environmental factors such as temperature and humidity. Special attention is given to the overwintering stages of the cabbage aphid, revealing that it survives in egg, larval, and adult forms within plant residues and cruciferous weeds. Early spring observations demonstrated the rapid activation and population growth of aphids, with peak reproduction occurring in moderate temperature conditions. Laboratory experiments showed that the average fecundity of a single aphid reached 39 larvae, with maximum productivity observed in spring and autumn seasons. In addition, the bioecological features of the cabbage bug were investigated, including its feeding behavior, egg-laying patterns, embryonic development, and larval stages. The results indicate that environmental conditions significantly influence its reproductive activity and development rate. The duration of development from egg to adult stage varies seasonally, being longer in spring and shorter in summer. The findings of this research contribute to a deeper understanding of pest population dynamics in cruciferous crops and provide a scientific basis for developing effective, environmentally friendly pest management strategies.